Effects of different tillage practices and cropping patterns on soil physical properties and crop productivity - Mohammed Abdus Salam; M.K.Alam, N.; Salahin; M.H. Rashid (Universiti Malaysia Kelantan, 2013)
A series of experiments using nine treatment combinations comprising three tillage practices (zero tillage, conventional tillage and deep tillage) and three cropping patterns (wheatfallow- T. aman, wheat–mungbean-T. aman and wheat-dhaincha-T. aman) were examined in a split- plot design at Bangladesh Agricultural Research Institute (BARI), Gazipur, Bangladesh during 2008-2009 and 2009-2010 to study the effect of different tillage practices and cropping patterns on soil physical properties and crop productivity in a previously puddled soil. Soil physical properties viz. bulk density, particle density and porosity showed insignificant result due to tillage practices and cropping patterns but soil moisture retentive properties demonstrated significant outcomes. Deep tillage with dhaincha (Sesbania rostrata) and mungbean (Vigna radiata L. Wilczek) biomass incorporation conserved moisture in the soil profile and improved other soil physical properties i.e. reduced the bulk density, increased porosity and available water content of soil. The highest grain yield of wheat and rice was recorded in the deep tillage with wheat-dhaincha-T. aman cropping pattern and lowest in zero tillage with fallow based cropping pattern.